2016
DOI: 10.1002/dvg.22990
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal differences in otoconial gene expression

Abstract: Otoconia are minute bio-crystals composed of glycoproteins, proteoglycans and CaCO3, and are indispensable for sensory processing in the utricle and saccule. Otoconia abnormalities and degeneration can cause or facilitate crystal dislocation to the ampulla, leading to vertigo and imbalance in humans. In order to better understand the molecular mechanism controlling otoconia formation and maintenance, we have examined the spatial and temporal expression differences of otoconial genes in the mouse inner ear at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Recently, expression of DMP1 was detected in the murine inner ear. The expression level was significantly higher in the utricle and saccule than in cochlea . DMP1 was also found in murine otoconia .…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Recently, expression of DMP1 was detected in the murine inner ear. The expression level was significantly higher in the utricle and saccule than in cochlea . DMP1 was also found in murine otoconia .…”
Section: Introductionmentioning
confidence: 84%
“…Studies of both the mouse and zebrafish model systems help to define how human otoconia form . As concentration of calcium ions is low (in the order of 0.1 mM), protein activity seems to be required for crystal seeding and growth . The organic components of otoconia are either the same or belong to the same family as bone matrix proteins, however, the expression levels are different and their roles in the crystal formation remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zebrafish ( Danio rerio ) have become an increasingly valuable vertebrate model system in toxicology 41,15 due to their high fecundity, external and transparent development, rapid generational times, reliance on evolutionarily conserved developmental regulatory gene networks, and sequenced genome, which facilitates mechanism-based toxicity studies. Like all vertebrate organisms, zebrafish have structural and sensory apparatus to perceive gravitational and positional cues for spatial awareness and posture control 16 , and perceive gravity and linear acceleration using mineralized biocrystals coupled to hair cells within the inner ear in a manner similar to other vertebrates, including humans. 16 In zebrafish, these biocrystals are consolidated into three distinct and large structures termed otoliths that each directly interact with an entire patch of sensory epithelium located in the saccule, utricle, and a non-mammalian specific otolithic region known as the lagena 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Like all vertebrate organisms, zebrafish have structural and sensory apparatus to perceive gravitational and positional cues for spatial awareness and posture control 16 , and perceive gravity and linear acceleration using mineralized biocrystals coupled to hair cells within the inner ear in a manner similar to other vertebrates, including humans. 16 In zebrafish, these biocrystals are consolidated into three distinct and large structures termed otoliths that each directly interact with an entire patch of sensory epithelium located in the saccule, utricle, and a non-mammalian specific otolithic region known as the lagena 6 . The formation of otoliths in zebrafish has not yet been completely characterized but studies in trout and other species have shown that daily variations in the composition of vestibular endolymph are required 8,9 .…”
Section: Introductionmentioning
confidence: 99%